2019
DOI: 10.1002/jts.22378
|View full text |Cite
|
Sign up to set email alerts
|

Moral Injury and Spiritual Struggles in Military Veterans: A Latent Profile Analysis

Abstract: War‐related traumas can lead to emotional, relational, and spiritual suffering. Drawing on two community samples of war zone veterans from diverse military eras (Study 1, N = 616 and Study 2, N = 300), the purpose of this study was to examine patterns of constellations between outcomes related to moral injury (MI) and common ways in which veterans may struggle with religion or spirituality, defined as divine, morality, meaning, interpersonal, and doubt. Results from latent profile analyses revealed three disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 24 publications
1
49
0
Order By: Relevance
“…The core characteristics of MI have not yet reached universal consensus (Kelley et al 2019). Notwithstanding this, MI is often theorized as resulting in shame, guilt, distrust, anger, grief, turmoil with God or a higher power, self-condemnation, and disgust (Bryan et al 2014;Currier et al 2019;Jinkerson 2016;Litz et al 2009;Shay 2014). MI can be self-directed (individual perpetrated an act that led to a transgression of moral boundaries) or other directed (witnessing or hearing about a transgression; Schorr et al 2018) and is linked with suicidality (suicidal ideation, plans, behaviour, and/or attempt) in veterans (Bryan et al 2014;2018).…”
Section: About Moral Injurymentioning
confidence: 99%
“…The core characteristics of MI have not yet reached universal consensus (Kelley et al 2019). Notwithstanding this, MI is often theorized as resulting in shame, guilt, distrust, anger, grief, turmoil with God or a higher power, self-condemnation, and disgust (Bryan et al 2014;Currier et al 2019;Jinkerson 2016;Litz et al 2009;Shay 2014). MI can be self-directed (individual perpetrated an act that led to a transgression of moral boundaries) or other directed (witnessing or hearing about a transgression; Schorr et al 2018) and is linked with suicidality (suicidal ideation, plans, behaviour, and/or attempt) in veterans (Bryan et al 2014;2018).…”
Section: About Moral Injurymentioning
confidence: 99%
“…Research to date has generally confirmed the initial constructs while providing more knowledge on the associations between certain types of PMIEs and their MI outcomes. For example, self‐directed PMIEs have been associated with shame and guilt; self‐blame; feelings of being unlovable, unforgivable, or incapable of moral decision‐making; and self‐handicapping behaviors (Currier, Foster, & Isaak, [this issue]). Betrayal, on the other hand, has been associated with anger, moral disgust, beliefs and attitudes related to mistrust of others, and revenge fantasies for the responsible person or persons (Currier, Foster et al., ).…”
Section: Outcomes Of Moral Injurymentioning
confidence: 99%
“…Clinicians should attend to the role that gambling plays in the lives of veterans and address the religious and spiritual struggles that arise from problem gambling. Currier, Foster, and Isaak (2019) are provided for comparison to a non-clinical sample. The demonic struggles subscale was not administered in the Currier, Foster, and Isaak (2019) study.…”
Section: Resultsmentioning
confidence: 99%
“…for meaning-related struggles, the decrease was medium, t(156) = 6.37, p ≤ .001, d = .54; and for moral struggles, the decrease was small, t(156) = 4.09, p ≤ .001, d = .37. Table 1 also presents findings from an administration of the RSS (excluding demonic struggles) to veterans (N = 616) conducted by Currier, Foster, and Isaak (2019). These figures provide an appropriate benchmark for comparing spiritual struggles among a non-clinical sample of veterans to those who participated in our study.…”
Section: 2mentioning
confidence: 99%